Histochemistry profile of the biceps brachii muscle fibres of capuchin monkeys (Cebus apella, Linnaeus, 1758) - Bortoluci, Carlos Henrique Fachin; Simionato, Luis Henrique; Rosa Junior, Geraldo Marco; Oliveira, José Américo de [UNESP]; Lauris, José Roberto Pereira; Moraes, Luis Henrique Rapucci; Rodrigues, Antonio de Castro; Andreo, Jesus Carlos (Int Inst Ecology, 2014)
A general analysis of the behaviour of "Cebus" shows that when this primate moves position to feed or perform another activity, it presents different ways of locomotion. This information shows that the brachial biceps muscle of this animal is frequently used in their locomotion activities, but it should also be remembered that this muscle is also used for other development activities like hiding, searching for objects, searching out in the woods, and digging in the soil. Considering the above, it was decided to research the histoenzimologic characteristics of the brachial biceps muscle to observe whether it is better adpted to postural or phasic function. To that end, samples were taken from the superficial and deep regions, the inserts proximal (medial and lateral) and distal brachial biceps six capuchin monkeys male and adult, which were subjected to the reactions of m-ATPase, NADH-Tr. Based on the results of these reactions fibres were classified as in Fast Twitch Glycolitic (FG), Fast Twitch Oxidative Glycolitic (FOG) and Slow Twitc (SO). In general, the results, considering the muscle as a whole, show a trend of frequency FOG>FG>SO. The data on the frequency were studied on three superficial regions FOG=FG>SO; the deep regions of the inserts proximal FOG=FG=SO and inserting the distal FOG>FG=SO. In conclusion, the biceps brachii of the capuchin monkey is well adapted for both postural and phasic activities.

Uma análise geral do comportamento do “Cebus apella” mostra que este primata quando desloca para se alimentar ou realizar outra atividade apresenta diferentes maneiras de locomoção. Estas informações mostram que o músculo bíceps braquial deste animal é usado freqüentemente nas suas atividades de locomoção, mas deve ser lembrado ainda que este músculo é usado também para desenvolvimento de outras atividades como esconder-se, procurar objetos, vasculhar arboredos, além de cavar o chão. Considerando-se o exposto acima decidiu-se pesquisar as características histoenzimológicas do músculo bíceps braquial do macaco-prego com o objetivo de comparar se este músculo esta melhor adaptado para funções posturais ou fásicas. As amostras foram retiradas das regiões superficiais e profundas; inserções proximais (medial e lateral) e distal de seis macacos-prego machos e adultos, os quais foram submetidos às reações de m-ATPase, NADH-Tr. Baseado nos resultados das reações, as fibras foram classificadas em Fast Twitch Glycolitic (FG), Fast Twitch Oxidative Glycolitic (FOG) e Slow Twitch (SO). Quanto à área dos diferentes tipos de fibras, os resultados encontrados foram semelhantes em todas as amostras estudadas, e as fibras de contração rápida foram sempre maiores do que as de contração lenta (FG=FOG>SO). Os dados obtidos sobre a frequência foram: nas três regiões superficiais estudadas FOG=FG>SO; nas regiões profundas das inserções proximais FOG=FG=SO e na inserção distal FOG>FG=SO. Baseado nestes dados pode-se concluir que o músculo bíceps braquial do macaco-prego está bem adaptado tanto para atividades posturais como fásicas.
Perfil histoquímico das fibras do músculo bíceps braquial do macaco-prego (Cebus apella, Linnaeus, 1758)
Keywords: Biceps brachii muscle; Histoenzimologic; Muscle fibre types; Capuchin monkeys; Primates; Músculo bíceps braquial; Histoenzimologia; Tipos de fibras musculares; Macaco-prego; Primatas